Novel homozygous silent mutation of ITGB3 gene caused Glanzmann thrombasthenia - Wang, Zhengrong; Xu, Yuqing; Sun, Yixi; Wang, Shuang; Dong, Minyue (Frontiers in Pediatrics, 2023)
Glanzmann thrombasthenia (GT) is a rare inherited disease characterized by mucocutaneous bleeding due to the abnormalities in quantity or quality of platelet membrane GP IIb (CD41) or GP IIIa (CD61). GP IIb and GP IIIa are encoded by the ITGA2B and ITGB3 genes, respectively. Herein, we described a 7-year-old Chinese boy of the consanguineous couple who was diagnosed with GT based on the typical clinical manifestations, absence of blood clot retraction and the reduced expression of CD41 and CD61 in platelets. A homozygous silent variant c.1431C>T (p. G477=) of the ITGB3 gene was identified by the Whole-exome sequencing and confirmed by Sanger sequencing. The variant was predicted to affect the splicing. RT-PCR and sequencing revealed that the variant caused a deletion of 95 base pairs and frameshift, and subsequently created a premature stop codon in exon 10 of ITGB3 (p. G477Afs*30). It was indicated that the variant c.1431C>T (p. G477=) of ITGB3 was the cause for Glanzmann thrombasthenia. Our findings expanded the mutation spectrum and provided the information for the genetic counseling, prenatal diagnosis and preimplantation genetic testing (PGT).